ChemInform Abstract: Highly Efficient Rhenium‐Catalyzed Deoxygenation of Sulfoxides Without Adding Any Reducing Agent. Issue 9 (5th March 2013) - Sousa, Sara C. A.; Bernardo, Joana R.; Romao, Carlos C.; Fernandes, Ana C.
Abstract The novel method is highly efficient for aromatic and aliphatic sulfoxide substrates.